Developmet Of WE-ARe Based Teaching Modules on Flood Disaster Mitigation Material to Train Students' Scientific Literacy - Siti Nur Khasanah; Kiki Septaria; Silvi Rosiva Rosdiana (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Recent declines in Indonesian students' scientific literacy, exacerbated by the post-pandemic learning loss and inadequate teaching materials, necessitate innovative instructional solutions. While contextual learning improves student engagement, the integration of the WE-ARe (Warm-up, Exploring, Argumentation, Resume) approach specifically into flood disaster mitigation modules remains underexplored in current literature. Therefore, this study aims to develop and evaluate the feasibility, instructional implementation, and effectiveness of a WE-ARe-based teaching module on students' scientific literacy. This Research and Development (R&D) study adopted the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The researchers selected 26 eighth-grade students at MTs Maslakul Huda as the research sample using a purposive sampling technique. Furthermore, the researchers collected data through expert validation questionnaires, instructional observation sheets, and scientific literacy tests. The results demonstrated high product feasibility, with validation scores from material (83.33%), media (75.00%), and language experts (85.71%) indicating strong validity. During the intervention, the instructional implementation achieved an excellent category average of 92.00%. Finally, the paired sample t-test revealed a significant improvement in students' scientific literacy (p = 0.001 < 0.05). In conclusion, the WE-ARe-based flood mitigation module provides a valid, highly implementable, and effective pedagogical tool to elevate students' scientific literacy, offering a scalable framework for disaster-resilient science education.